Retained placenta after vaginal delivery: risk factors and management - Perlman NC; Carusi DA (Dove Medical Press, 2019)
Nicola C Perlman, Daniela A Carusi Department of Obstetrics and Gynecology, Brigham and Women’s Hospital, Harvard Medical School, Boston, MA, USACorrespondence: Daniela A CarusiDepartment of Obstetrics and Gynecology, Brigham and Women’s Hospital, Harvard Medical School, 75 Francis St, Boston, MA 02115, USATel +1 617 732 5452Fax +1 617 232 6346Email dcarusi@bwh.harvard.eduAbstract: Retained placenta after vaginal delivery is diagnosed when a placenta does not spontaneously deliver within a designated amount of time, variably defined as a period of 18–60 mins. It may also be diagnosed if a patient experiences significant hemorrhage prior to delivery of the placenta. Normal placenta delivery requires adequate uterine contractions, with shearing of the placenta and decidua from the uterine wall and expulsion of the tissue. Thus, retained placenta can occur in the setting of significant uterine atony, abnormally adherent placenta, as with placenta accreta spectrum (PAS), or closure of the cervix prior to placental expulsion. Risk factors for retained placenta parallel those for uterine atony and PAS and include prolonged oxytocin use, high parity, preterm delivery, history of uterine surgery, and IVF conceptions. History of a prior retained placenta and congenital uterine anomalies also appear to be risk factors. Management entails manual removal of the placenta with adequate analgesia, as medical intervention alone has not been proven effective. Complications can include major hemorrhage, endometritis, or retained portions of placental tissue, the latter of which can lead to delayed hemorrhage or infection. Prophylactic antibiotics can be considered with manual placenta removal, though evidence regarding effectiveness is inconsistent. If hemorrhage is encountered, deployment of a massive transfusion protocol, uterine evacuation with suction, and use of intrauterine tamponade, as with an intrauterine balloon, should be initiated immediately. When a separation plane between the placenta and uterus is particularly difficult to create, PAS should be considered, and preparations should be made for hemorrhage and hysterectomy. Patients with risk factors for retained placenta should have a laboratory sample sent for blood type and antibody screening on admission to labor and delivery, and plans should be made for appropriate analgesia and preparations for hemorrhage if a retained placenta is encountered.Keywords: retained placenta, manual removal of the placenta, postpartum hemorrhage, placenta accreta spectrum